MAXIM FLOUTING IN “BROOKLYN NINE-NINE” - Michelia Kanzha Novera; Winaya I Made; Udayana I Nyoman (IKIP Siliwangi, 2021)
This study aims at identifying the types of maxims flouted by the main characters of “Brooklyn Nine-Nine” and describing the context behind those floutings. The data were taken from the fourth season of “Brooklyn Nine-Nine”, an American police procedural comedy TV show. Documentation method was used to collect the data. Descriptive qualitative method was used to analyze the data by applying Grice’s Cooperative Principle (1975) and Cutting’s Theory of Context (2002). Based on the analysis, all types of conversational maxims were flouted, namely maxim of quantity, maxim of quality, maxim of relation, and maxim of manner. Another finding in this research is that the context behind the floutings were needed to understand the meaning of the utterances. Keywords: Context, Maxim Flouting, Pragmatics